Digital Madrasah and Student Mental Health: Exploring the Psychological Impacts of E-Learning in Islamic Schools - Chyono, Intim; Palupi, Jenie; Maryanti, Syiska Atik; Setyorini, Dhiana (Yayasan Minang Darussalam, 2025)
This study explores the psychological impacts of e-learning on student mental health in digital madrasahs (Islamic schools). With the rapid integration of digital platforms in education, particularly in religious settings, the study examines how the shift from traditional face-to-face learning to digital learning environments has influenced students' emotional well-being, stress levels, and overall mental health. The research focuses on the unique challenges faced by students in madrasahs, where religious and academic education are blended with digital tools and online resources. Using a mixed-methods approach, both qualitative and quantitative data were collected through surveys, interviews, and psychological assessments of students. The findings reveal that while e-learning offers flexibility and accessibility, it also presents significant challenges, including increased screen time, social isolation, and difficulty in maintaining focus, all of which negatively affect students' mental health. Additionally, the study identifies coping mechanisms adopted by students and the role of teachers and school administrators in mitigating mental health risks. This research contributes to the growing body of literature on digital education and mental health, particularly in the context of Islamic education, and offers recommendations for creating supportive digital learning environments in madrasahs.